Policy advice in development cooperation: a distinct type of policy advice - Christian von Haldenwang; Marianne Alker (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
While development cooperation (DC) is determined to make more and more use of policy advice to reach its goals, it does not always have a clear conception of what policy advice is actually able and meant to accomplish in the development context. Experts often lack the conceptual knowledge needed to successfully advise political actors and institutions in a partner country. New modalities of policy advice have been slow to gain traction in DC. The available concepts are geared in large measure to scientific policy advice or to the ways in which the role of DC experts has traditionally been understood. However, this conception applies only to one subarea of policy advice in DC. In order to engage in policy advice in a meaningful manner, DC should rely increasingly on approaches that combine personal contacts to high-ranking decisionmakers with institutional capacity development. Planning cycles in DC should be more closely linked to political cycles in partner countries. Experts should be trained in political analysis and public policy management in a developing country context. Also, there is a need to strengthen monitoring and evaluation with regard to the quality of political processes.
Keywords: 330